The Unwinding of Circular Deoxyribonucleic Acid by Phenanthridinium Drugs: Structure-Activity Relations for the Intercalation Reaction - WAKELIN, L.P.G.; WARING, M.J. (Molecular pharmacology, 1974)
The interaction between a series of phenanthridinium drugs and bacteriophage PM2 circular DNA has been studied with the object of investigating how substituents on the phenanthridine chromophore affect its capacity to intercalate between the DNA base pairs. Variations in the quaternising group at position 5 have little or no effect. The presence of a phenyl substituent at position 6 strongly influences external attachment to the DNA helix and affects the unwinding angle. Introduction of a p-carboxyl group on the phenyl ring leads to weaker binding. Free primary amino groups at positions 3 and 8 are not mandatory for the intercalation reaction, but their presence adds stability to the complex (approximately 1.7 kcal/mole). Removal of the 3-amino group has little effect other than a small reduction in the unwinding angle, whereas acetylation of the 8-amino gruop results in weaker binding as well as a lowered unwinding angle. Replacement of both 3- and 8-amino groups by carbethoxyamino substituents leads to markedly weaker binding and an apparent unwinding angle of only 5.1° ± 0.6°, the lowest value observed with any phenanthridine, together with other consequences which suggest a radical alteration in the mechanism of binding to DNA. Introduction of bromine atoms in place of amino groups at positions 3 and 8 yields a heavy-atom derivative which still unwinds the DNA helix by the same angle as ethidium at low ionic strength. Structure-activity correlations for the intercalation reaction deduced from these studies are in agreement with earlier findings relating to antimicrobial activity. ACKNOWLEDGMENTS We thank and Mr. N. F. Totty for skilled technical assistance, and many colleagues for helpful advice and criticism. We are especially grateful to Drs. R. Slack, S. S. Berg, and G. Woolfe for generous supplies of the drugs, together with precise analytical data on their chemical constitution.